GAMBARAN PENGETAHUAN DAN SIKAP TERHADAP PERILAKU PEMELIHARAAN KESEHATAN GIGI DAN MULUT SISWA SMK KECAMATAN AGRABINTA (Politeknik Kesehatan Kemenkes Bandung, 2021)
According to the 2018 Basic Health Research, the most common dental and oral health problem in the community is caries (45.7%), this is because people do not understand how to maintain good and correct oral health behavior. This behavior can occur due to lack of knowledge and attitudes of the community itself towards the behavior of maintaining oral health. This study aims to describe the knowledge and attitudes of students of SMKN 1 Agrabinta, majoring in OTKP (Office Administration Automatization) in class 10 towards dental and oral health maintenance behavior. The research method used is descriptive research. The population of this study were 180 students of SMKN 1 Agrabinta with sampling calculated using the Slovin formula so that a sample of 22 respondents was obtained. The results showed that the respondents' knowledge of dental and oral health maintenance behavior was categorized as high with 11 respondents (50%), 10 respondents in moderate criteria (45.5%) and 1 respondent with low criteria (4.5%). For attitudes towards dental and oral health maintenance behavior, as many as 20 respondents (90.9%) had a good attitude and 2 respondents (9.1%) had a moderate attitude. This shows that most of the respondents' knowledge and attitudes towards dental and oral health maintenance behavior are categorized as good.